Web 2.0 enabled knowledge sharing practices among students of IIUM : an exploration of the determinants - Usman, Shuaibu Hassan (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2014)
Knowledge sharing using web enable technologies is becoming more and more important as such educational institutions are trying to harness this opportunity to students' learning environment in order to create value. Therefore, the aim of this research is to conduct an empirical study to explore the factors that influence the success of knowledge-sharing using web 2.0 technologies among students in IIUM. This study is poised to the theoretical understanding of web technologies that enable knowledge sharing and learning in today's educational settings. Social Identity theory and Social Dilemma theory as a kind of knowledge sharing were used in developing the research model. In this study, a semi-structured questionnaire was used to collect data in which 287 respondents answered the items on the questionnaire. Descriptive statistics, multiple regression analysis, and one-way ANOVA were employed in data analysis. The results of descriptive statistics show that students give preference to those tools with good user interface and easy to use, students prefer some features of the web 2.0 tools than others to share their knowledge, and students use web 2.0 tools including social networking sites like Facebook for academic purposes. In addition, the results reveal that the quality of knowledge sharing can be improved through good user interface design, communication features, collaboration features, creating awareness and training, providing learning facilities and materials, fast internet connectivity, and motivation. On the other hand, the outcomes of the regression analysis indicate that individual, organizational, and technological factors influence students to use web 2.0 to share knowledge. Benefits that the students expect to obtain and students' experience from using the web 2.0 enabled knowledge sharing emerged to be influencing knowledge sharing. Similarly, workgroup and knowledge culture significantly influence web 2.0 enabled knowledge sharing practices among students of IIUM. Lastly, technology availability and technology support were found to have positive effect in influencing web 2.0 enabled knowledge sharing practices among students in the university. The results of one-way ANOVA confirm that individual, organizational, and technological factors differ in influencing web 2.0 enabled knowledge sharing practices among students in the university